Sufficiently good measures of obesity: The case of a developing country - Sohn, Kitae (Cambridge University Press, 2014)
Copyright © 2014 Cambridge University Press.Obesity is pandemic, but no consensus has yet emerged regarding appropriate tools for measuring it. Medical research based on populations in the developed world has largely dismissed body mass index (BMI) because it is a weak predictor of some health outcomes. In contrast, social science research still relies on it for its simplicity and ready availability in surveys. This paper uses consistent definitions and measures to select sufficiently good predictors of health and economic outcomes from among the anthropometrics that are considered alternatives to BMI. The results from the Indonesian Family Life Survey indicate that BMI and waist circumference are better predictors than waist-to-height ratio and waist-to-hip ratio. This paper argues that given its advantages, BMI is an adequate measure of obesity for Indonesia and possibly for the developing world. Further, if BMI is to be replaced, waist circumference is preferable to other anthropometrics.